Computer networks - Tanenbaum, Andrew S. (New Jersey Prentice Hall, 2003)
Contents: Introduction; the physical layer; the data link layer; the medium access control sublayer; the network layer; the transport layer; the application layer; network security; reading list and bibliography.
Includes index
Keywords: Công nghệ thông tin